Rivoluzione mobiletica e relazioni sociali nel mondo urbano - DOI: 10.5752/P.2316-1752.2009v16n18/19p227 - Scidà, Giuseppe (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract This paper deals with some tangible consequences of the mobiletic revolution, a necessary - but not exhaustive - catalyst to the full development of the globalization process, whose effects have deep repercussions on the social, economic and territorial organization of social systems both nationwide and worldwide. The overall results seem to express a new global society experiencing a sharp drop in space friction, with relevant consequences on human settlements, social relations, and people’s and goods’ mobility in space. Key words : Mobiletic revolution; Social change; Social relations; Urban transition.